Analysis and Solutions in the Light of Islamic Thought - Rabbi, Asma; Bhatti, Irfan Hassan; Rasheed, Tayiba (sourcecoder, 2024)
The upbringing of children is a fundamental pillar of human society. It is a core necessity of every social system, influencing not only the physical and mental development of children but also shaping their moral, spiritual, and social dimensions. Islamic teachings regard the upbringing of children as a significant responsibility aimed at producing virtuous individuals and creating an ideal society. In an Islamic social framework, the role of social institutions in child upbringing is extremely crucial, as these institutions are tasked with imparting fundamental values and life skills to children. According to Islamic teachings, the process of nurturing children is recognized as a shared responsibility of parents, teachers, and other social institutions. This responsibility is not confined to a single generation but is passed from one generation to the next, with the ultimate goal of fostering virtuous individuals and establishing an exemplary society.